INTEGRATION OF PUTRIKĀ AND SENTANA RAJEG IN BALINESE CUSTOMARY INHERITANCE LAW: A GENDER EQUALITY PERSPECTIVE - I Gusti Ayu Jatiana Manik Wedanti; I Gusti Ngurah Sudiana; I Made Dian Saputra (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
This article explores the intersection of the putrikā provision in Hindu law and the sentana rajeg practice in Balinese customary law through the lens of gender equality in inheritance. Putrikā, as articulated in the Manava Dharmasastra, legitimizes the appointment of daughters as heirs in the absence of sons, preserving both lineage (gotra) and religious duties. Likewise, sentana rajeg enables daughters to assume hereditary roles within Balinese adat, including through nyentana marriages. This study applies a normative legal methodology incorporating conceptual, historical, and statutory approaches. It finds that both legal traditions, despite their patriarchal foundations, contain adaptive mechanisms that acknowledge female inheritance under certain conditions. These mechanisms reflect a legal pragmatism oriented toward maintaining familial and spiritual obligations. From a modern human rights perspective, these customary norms require reinterpretation to align with principles of substantive gender equality. Strengthening women’s inheritance rights not only promotes justice within traditional societies but also reinforces the legitimacy and adaptability of customary law in a globalized context. The article argues for collaborative legal reform involving customary authorities, state institutions, scholars, and civil society to create inclusive, equitable inheritance frameworks that respect both tradition and contemporary gender norms.